2016
DOI: 10.12783/issn.1544-8053/13/3/7
|View full text |Cite
|
Sign up to set email alerts
|

Modified Electro-spun Polyvinyl Alcohol Nanofibers Used as Super Adsorbing Material for Lead Ions in Aqueous Solution

Abstract: Polyvinyl alcohol nanofibers (PVA) and novel polyvinyl alcohol nanofibers incorporated with cobalt metal organic framework (PVA/Co-MOF) sorbents were produced via electrospinning. The produced nanofibers were confirmed by scanning electron microscope (SEM), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR). SEM images showed consistent and beads free nanofibers were synthesized. FTIR spectra's exhibited shifts in critical functional groups positions thus it confirmed that there was a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The maximum bed loading capacity for 1 mg/L Cr(VI) filtration at the breakthrough point was found to be 16.5 mgchromium/g-chitosan, higher than the static adsorption capacity of 11.0 mg-chromium/g-chitosan using nanofiber mats, indicating the membranes' better potential for dynamic adsorption. Shooto et al (2016) fabricated nanofibers via electrospun, from polyvinyl alcohol (PVA) and PVA incorporated with metal (Co) organic framework (PVA-Co-MOF), and investigated the ability of these fibers to remove Pb(II) ions from water. It was reported that the sorption of Pb 2+ ions on PVA-Co-MOF) were twice as compared to the PVA nanofiber.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…The maximum bed loading capacity for 1 mg/L Cr(VI) filtration at the breakthrough point was found to be 16.5 mgchromium/g-chitosan, higher than the static adsorption capacity of 11.0 mg-chromium/g-chitosan using nanofiber mats, indicating the membranes' better potential for dynamic adsorption. Shooto et al (2016) fabricated nanofibers via electrospun, from polyvinyl alcohol (PVA) and PVA incorporated with metal (Co) organic framework (PVA-Co-MOF), and investigated the ability of these fibers to remove Pb(II) ions from water. It was reported that the sorption of Pb 2+ ions on PVA-Co-MOF) were twice as compared to the PVA nanofiber.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…Conversely, a slight peak shift is observed at PVAM composite membrane (Figure S1b, curve b′), as compared to that of the pure PVAM nonwoven membrane. The peaks shift are mainly due to the Lewis acid–base interaction between the LATP filler (as a Lewis acid) and PVAM (as a Lewis base, −OH group side chain in PVA) polymer segments …”
Section: Resultsmentioning
confidence: 99%
“…The peaks shift are mainly due to the Lewis acid−base interaction between the LATP filler (as a Lewis acid) and PVAM (as a Lewis base, −OH group side chain in PVA) polymer segments. 39 Figure S1c shows the TGA curves of the PVAM composite membrane (curve a′) and pure PVAM membrane (curve b′). Three stages of weight loss were observed in the TGA curve for both the as-prepared PVAM composite membrane and the pure PVAM membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all adsorption kinetics are better matched with the pseudo-second-order model, as evidenced by the better correlation coefficients compared to the pseudo-rst-order model. 89,90,93 In a study by Peng et al, 85 the adsorption data of ZIF-8-PAN NF for Cu(II) were adapted to a pseudo-second-order model (R 2 ¼ 0.967). The agreement of the kinetic data with this kinetic model suggests that the adsorption of HMIs on MOFs in aqueous solutions can be controlled by chemical adsorption.…”
Section: Removal Mechanism and Kineticsmentioning
confidence: 99%
“…Shooto et al 90 described an electrospinning method for producing PVA–Co-MOF sorbents by combining novel PVA nanofibers with a cobalt metal–organic framework. SEM images showed that homogeneous, bead-free nanofibers were developed.…”
Section: Hmis Removal Via Mof-based Nanofibers Mat...mentioning
confidence: 99%